Phytoplankton morphospecies of el cometa lagoon in the biosphere reserve of pantanos de Centla - Esqueda-Lara, Karina; Sánchez, Alberto J.; Salcedo, Miguel Ángel; Rincones-Reyes, Karla Margarita; Popoca-Cruz, Pavel E. (Ecosistemas y Recursos Agropecuarios, 2021)
El Cometa lagoon lacks information on microalgae diversity, despite its relevance as the first productive component of aquatic ecosystems and its influence on water quality. Therefore, the objective of determine the morphospecies of phytoplankton microalgae in El Cometa lagoon, as well as, their indicator species and the possible presence of potentially toxic species were raised. Phytoplankton samples with 20 μm phytoplankton network were collected in six sites during rainy season. Fifty taxa from six taxonomic groups are the first records for the lagoon and Pantanos de Centla Biosphere Reserve. Thirty-three of them were added to the records for the coastal plain of the Usumacinta River. Five were marine, seven potentially toxic and five bioindicators of contamination and eutrophication conditions that represent a public health risk.